ANALYSIS OF STUDENTS' 4C SKILLS BASED ON THE PEDAGOGY MULTILITERACIES MODEL - Muhammad Nawawi; Muawwinatul Laili; Ana Christanti (Jurnal Scientia, 2022)
This research aims to analyze the students’ 4C skills based on the Pedagogy Multiliteracies model implemented by the teachers in the classroom. The teachers are not familiar yet with the pedagogy multiliteracies model by Cope and Kalantzis which has four syntaxes of teaching; Situated Practice, Overt Instruction, Critical Framing, and Transformed Practice. The researchers need to reveal how the teachers’ teaching process is based on the model then relate them to the students’ 4C skills. The subjects of the research are the teachers of English, Mathematics, and Bahasa Indonesia from two Senior High Schools in Sidoarjo. There are six teachers; three from the state and another from the private school. They belong to the best schools in the city. Observation, interviews, and questionnaires are used to collect the research data. The research shows that the student's critical thinking, creativity, and communication skills were on the low level since the teachers did not implement the teaching-learning process as the concept of the multiliteracies model yet. The collaboration skills were good enough since the teachers often design group works to complete the tasks. The teachers should try to teach using the multiliteracies pedagogy framework to enhance the students’ 4C skills in this century.